Evaluation of the Good Review Practices of Countries Participating in the Southern African Development Community: Alignment and Strategies for Moving Forward - Sithole, Tariro; Mahlangu, Gugu; Capote, Velma; Sitoie, Tania; Shifotoka, Saren; Gaeseb, Johannes; Padayachee, Silverani; Sehloho, Tohlang; Khea, Akida; Fimbo, Adam; Munkombwe, Zuma; Mwale, Bernice; et al. (Frontiers in Medicine, 2021)
Introduction: National medicines regulatory agencies are faced with challenges including limited resources and technical capacity, resulting in countries collaborating and sharing resources to improve efficiency of the review process to facilitate access to quality-assured medicines by their populations. One such collaboration is the Southern African Development Community (SADC) medicines registration collaborative initiative, ZaZiBoNa. Countries participate in the initiative by contributing to regulatory reviews and good manufacturing practices inspections. The aim of this study was to review and compare the registration processes of regulatory authorities of Mozambique, Namibia, South Africa, Tanzania, Zambia and Zimbabwe to identify strategies for better alignment. Methods: A senior member of the division responsible for issuing marketing authorisations completed an established validated questionnaire, which standardises the review process, allowing key milestones, activities and practices of the six regulatory authorities to be identified and compared. The completed questionnaires were validated by the heads of the respective agencies. Results: The six countries vary in population and in the size of their respective regulatory agency and the resources allocated to regulatory reviews. The review processes of the six agencies were similar; however, differences were noted in the milestones recorded; for example, two of the countries did not record the start of the scientific assessment. Additionally, decisions for marketing authorisation were made by an expert committee in four of the countries and by the head of the agency and the Minister of Health in two countries. All six agencies implemented the majority of good review practices; however, the need for improvement in the areas of transparency and communication and good-quality decision making was a common finding for all six countries. Conclusions: Participation in the ZaZiBoNa initiative has improved the way in which the six agencies perform regulatory reviews in their countries, highlighting the realisation of one of the key objectives of the initiative, which was building the expert capacity of member countries. Other agencies in the SADC region and beyond can use the results of this study to identify best practices, which in turn, could improve their regulatory performance.